If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2n + n + 6n + 2 = 11 Reorder the terms: 2 + 2n + n + 6n = 11 Combine like terms: 2n + n = 3n 2 + 3n + 6n = 11 Combine like terms: 3n + 6n = 9n 2 + 9n = 11 Solving 2 + 9n = 11 Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + 9n = 11 + -2 Combine like terms: 2 + -2 = 0 0 + 9n = 11 + -2 9n = 11 + -2 Combine like terms: 11 + -2 = 9 9n = 9 Divide each side by '9'. n = 1 Simplifying n = 1
| 3-2ax-2/3a-2/3x | | 13r+-4r+-12=6 | | 14w=9w+35 | | Y=4x^2+196-11 | | m^-5/2=1/2048 | | 5(3)-3y=3 | | 11y-5=2y+24 | | X+5+60+x=180 | | 2x+x+40+x+20=180 | | 54x+5y-5z=91 | | 1.37=(x^3)/(x^2) | | 16b-12-3b=14 | | 36-x=8 | | f(x)=f(x-4)+f(2x-1) | | 14x+-13x=7 | | 12y-7y=45 | | 2(s-5)-6=4 | | 28+(8+x)=36 | | x^5=5x^4 | | 3(d-4)+1=10 | | 2x+57=119 | | 2(g+2)=6 | | -3u-11u=-14 | | -15g+3g=12 | | 3(u+1)+1=13 | | 34=2y+8 | | 14-2f=10 | | 5w+1.5=4.5 | | -10t+-t-9t+4=-16 | | J+4=8 | | 6+x=62 | | -3-X-60=20 |